Endoplasmic reticulum and mitochondrial calcium handling dynamically shape slow afterhyperpolarizations in vasopressin magnocellular neurons - Kirchner, Matthew K.; Althammer, Ferdinand; Campos-Lira, Elba; Montanez, Juliana; Stern, Javier E. (The journal of neuroscience, 2024)
Many neurons including vasopressin (VP) magnocellular neurosecretory cells (MNCs) of the hypothalamic supraoptic nucleus (SON) generate afterhyperpolarizations (AHPs) during spiking to slow firing, a phenomenon known as spike frequency adaptation. The AHP is underlain by Ca2+-activated K+ currents, and while slow component (sAHP) features are well described, its mechanism remains poorly understood. Previous work demonstrated that Ca2+ influx through N-type Ca2+ channels is a primary source of sAHP activation in SON oxytocin neurons, but no obvious channel coupling was described for VP neurons. Given this, we tested the possibility of an intracellular source of sAHP activation, namely, the Ca2+-handling organelles endoplasmic reticulum (ER) and mitochondria in male and female Wistar rats. We demonstrate that ER Ca2+ depletion greatly inhibits sAHPs without a corresponding decrease in Ca2+ signal. Caffeine sensitized AHP activation by Ca2+. In contrast to ER, disabling mitochondria with CCCP or blocking mitochondria Ca2+ uniporters (MCUs) enhanced sAHP amplitude and duration, implicating mitochondria as a vital buffer for sAHP-activating Ca2+. Block of mitochondria Na+-dependent Ca2+ release via triphenylphosphonium (TPP+) failed to affect sAHPs, indicating that mitochondria Ca2+ does not contribute to sAHP activation. Together, our results suggests that ER Ca2+-induced Ca2+ release activates sAHPs and mitochondria shape the spatiotemporal trajectory of the sAHP via Ca2+ buffering in VP neurons. Overall, this implicates organelle Ca2+, and specifically ER-mitochondria-associated membrane contacts, as an important site of Ca2+ microdomain activity that regulates sAHP signaling pathways. Thus, this site plays a major role in influencing VP firing activity and systemic hormonal release.
Gesehen am 07.04.2025